Ultra-sensitive class I tetramer analysis reveals previously undetectable populations of antiviral CD8+ T cells. - Barnes, E; Ward, S; Kasprowicz, V; Dusheiko, G; Klenerman, P; Lucas, M (2004)
A major breakthrough in cellular immunology has been the development of HLA class I tetramers to analyze CD8(+) T cell responses. However, in many situations, including persistent virus infection, specific T cell responses are rarely detected using this technology. This raises the question of whether such responses are 'deleted' (or 'exhausted') or present below the conventional detection limit for class I tetramer staining. In particular, persistent hepatitis C virus (HCV) infection is characterized by very weak or apparently absent specific CD8(+) T cell responses, even though they are readily detectable in acute disease. Therefore, we assessed the use of anti-PE-labeled magnetic beads to enrich tetramer-positive HCV-specific T cells and identify previously undetectable populations. Using the enrichment technique, HCV-specific T cells could be detected in the majority of infected individuals, whereas these responses were not detected using conventional tetramer staining (8/15 vs. 1/15; p=0.01). Magnetic enrichment could reliably detect very rare HCV-specific responses at frequencies of >0.0011% of CD8(+) T cells (approximately 1/million PBMC), and phenotypic analysis of these rare populations was possible. Therefore, this direct ex vivo technique revealed the persistence of very low frequencies of virus-specific CD8(+) T cells during chronic virus infection and is readily transferable to the study of other viral, self- or tumor-specific T cells.